Sexually transmissible infections among female sex workers in Manado, Indonesia, using a multiplex polymerase chain reaction-based reverse line blot assay - Mawu, Ferra O; Davies, Stephen C; McKechnie, Michelle; Sedyaningsih, Endang R; Widihastuti, Asti; Hillman, Richard J (Sexual health, 2011)
Sexually transmissible infections (STIs) remain highly prevalent, and HIV is increasing, among female sex workers (FSWs) in Indonesia. Our aim was to determine the prevalence of, and risk factors for, STIs among FSWs in Manado, Indonesia. We recruited FSWs mainly at their workplace: they completed a questionnaire and provided a urine sample and self-collected vaginal swab. Samples were tested using multiplex polymerase chain reaction, followed by reverse line blot hybridisation. We recruited 221 FSWs, (median age: 25 years). During the previous 3 months, 30% reported never using condoms; only 2.7% always used condoms. Of 217 women with urine samples, 49% had a 'curable STI': 10.6% with gonorrhoea, 26.7% with chlamydia, 12.4% with Mycoplasma genitalium and 22.6% with trichomoniasis. Independent risk factors for gonorrhoea were: domiciled outside North Sulawesi (P = 0.001) and age 16-25 years (P = 0.02); for chlamydia: no prior history of STI symptoms (P = 0.003) and age 16-25 years (P = 0.02); for Mycoplasma genitalium: number of clients on last day of sex work (P = 0.004); for trichomoniasis: number of clients per week (P = 0.04). When these four infections were grouped as any 'curable STI', independent associations were: number of clients on the last day of sex work (P = 0.001), age 16-25 years (P = 0.02) and sex working for fewer than 2 years (P = 0.03). This is the first report of M. genitalium infection in Indonesia. The high prevalence of STIs and low condom use among these FSWs suggest their vulnerability to the HIV epidemic in Indonesia. They need enhanced interventions, including outreach screening, and periodic presumptive treatment.